Bureaucratic pluralism and the transformation of development cooperation - Erik Lundsgaarde (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
This paper discusses the role of sector-specific ministries as development cooperation providers. These actors have the potential to contribute assets such as funding, expertise, or access to networks for global development efforts. However they may also present challenges for development bureaucracies by advancing alternative priorities or by complicating coordination efforts at headquarters and partner-country levels. The paper situates the analysis of donor bureaucracies in current discussions on aid and development effectiveness and the transformation of the Official Development Assistance (ODA) policy field and outlines questions to guide future research on this topic.
Keywords: 330; Aufstrebende Mächte; Deutsche + Europäische + multilaterale Entwicklungspolitik